Scattering of elastic waves by a general anisotropic basin. Part 1 a 2D model. - Dravinski, Marijan
Scattering of incident plane harmonic pseudo P-, SH and SV waves by a two dimensional basin of arbitrary shape is investigated by using an indirect boundary integral equation approach. The basin and surrounding half space are assumed to be generally anisotropic, homogeneous, linearly elastic solids. No material symmetries are assumed. The unknown scattered waves are expressed as linear combinations of full spae time harmonic two dimensional Green functions. Using the Radon transform, the Green functions are obtained in the form of finite integrals over a unit circle. An algorithm for the accurate and efficient numerical evaluation of the Green functions is discussed. A detailed convergence and parametric analysis of the problem is presented. Excellent agreement is obtained with isotrophic results available in the literature. Steady state surface ground motion is presented for semi circular basins with generally anisotropic material properties. The results show that surface motion strongly depends upon the material properties of the basin as well as the angle of incidence and frequency of the incident wave. Significant mode conversion can be observed for general triclinic materials which are not present in isotropic models. Comparison with an isotropic basin response demonstrates that anisotropy is very important for assessing the nature of surface motion atop basins.
Keywords: Two dimensional triclinic basin; Scattering; Site response